2016
DOI: 10.5871/jba/004.089
|View full text |Cite
|
Sign up to set email alerts
|

Social class mobility in modern Britain: changing structure, constant process

Abstract: The class structure provides an important context for the study of social mobility. The evolution of the class structure is the all-important factor determining individuals' changing experience of mobility, as expressed in absolute rates. The total mobility rate shows long-term stability; but, because of structural change, trends of rising upward and falling downward mobility in the mid-20th century are now being reversed. Relative mobility rates, comparing the chances of individuals of different class origins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(53 citation statements)
references
References 24 publications
0
51
0
2
Order By: Relevance
“…The selection process will be increasingly merit-based, with educational qualifications assuming greater importance for occupational attainment (Arrow B). There may be some exceptional circumstances, as in the case of highly educated people from poor families finding technical jobs (Hout, 1988) indicated by Arrow D or, as in Arrow E (Goldthorpe, 2016), of advantaged families finding good jobs via social contacts for their children who do not do well in education (although Gugushvili et al, 2017, show that the effect is limited). While debates abound, a common feature in these theories is that family origin is the most important influence on educational and occupational attainment.…”
Section: Introductionmentioning
confidence: 99%
“…The selection process will be increasingly merit-based, with educational qualifications assuming greater importance for occupational attainment (Arrow B). There may be some exceptional circumstances, as in the case of highly educated people from poor families finding technical jobs (Hout, 1988) indicated by Arrow D or, as in Arrow E (Goldthorpe, 2016), of advantaged families finding good jobs via social contacts for their children who do not do well in education (although Gugushvili et al, 2017, show that the effect is limited). While debates abound, a common feature in these theories is that family origin is the most important influence on educational and occupational attainment.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the 2005 data set did not capture the impact of the crisis and the subsequent recession (as well as that of other contemporary societal forces) on mobility outcomes in the EU. The outbreak of the 2008 world economic crisis marked the end of 'the golden age of upward social mobility' (Goldthorpe, 2016). Thus, the prospects of future welfare for younger generations have shrunk compared with the prospects of the older generations (Atkinson, 2015;Eurofound, 2017;OECD, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…3 For example, in 1830, around 27 percent of British children were enrolled in a primary school; by the late1960s, this had risen to almost 100 percent (Lindert 2004). However, many scholars have resisted this hypothesis. As noted in the introduction, the consensus view is that extensive educational reform has been remarkably ineffective in improving relative life chances, particularly in the United Kingdom (Boliver and Swift 2011;Goldthorpe 2016). Many argue that elite schools have been particularly adept at adapting and responding to such reform (Domhoff 2006;Levine 1980;Scott 1991;Stanworth and Giddens 1974).…”
mentioning
confidence: 99%
“…Yet an extensive body of research now offers a sobering corrective to this lofty ideal. Even though the widespread provision of free schooling has certainly reduced inequalities in educational attainment (Breen and Jonsson 2005), scholars working across a range of national contexts-but particularly in the United Kingdom and the United States-have found that the expansion of public education has largely failed to equalize relative opportunities in the labor market (Goldthorpe 2016;Parman 2011;Pfeffer and Hertel 2015;Rauscher 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation